2008
DOI: 10.1097/pas.0b013e318161d1a5
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and Molecular Evolutionary Pathways of Low Nuclear Grade Invasive Breast Cancers and Their Putative Precursor Lesions: Further Evidence to Support the Concept of Low Nuclear Grade Breast Neoplasia Family

Abstract: We have previously provided evidence showing an association between some precursor lesions with low nuclear grade breast carcinomas (LNGBCs). In this study, further immunophenotypic support to our proposed route of pathogenesis of LNGBC and their precursor lesions was provided. Precursor lesions including columnar cell lesions, atypical ductal hyperplasia, ductal carcinoma in situ, usual epithelial hyperplasia, and lobular neoplasia were compared with matching "morphologically normal" terminal lobular duct uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
126
2
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(147 citation statements)
references
References 39 publications
14
126
2
5
Order By: Relevance
“…Although not specifically addressed in this study, this combination may also be useful to better distinguish between papillomas secondarily involved by usual ductal hyperplasia and those secondarily involved by atypical ductal hyperplasia and/or ductal carcinoma in-situ, in a manner similar to their utility in discriminating between nonpapillary intraductal epithelial proliferations. 8,16,17 Another argument for using CK8/18 in the evaluation of papillary lesions is that its inclusion can provide a 'positive reaction' to support a diagnosis of malignancy (papillary carcinoma), instead of just a negative reaction that might be obtained with only CK5 (and/or p63). Of note, this latter rationale has been used to argue (successfully) for using amethylacyl-CoA racemase in the evaluation of atypical foci in prostate needle biopsy material, a widely accepted practice in contemporary surgical pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not specifically addressed in this study, this combination may also be useful to better distinguish between papillomas secondarily involved by usual ductal hyperplasia and those secondarily involved by atypical ductal hyperplasia and/or ductal carcinoma in-situ, in a manner similar to their utility in discriminating between nonpapillary intraductal epithelial proliferations. 8,16,17 Another argument for using CK8/18 in the evaluation of papillary lesions is that its inclusion can provide a 'positive reaction' to support a diagnosis of malignancy (papillary carcinoma), instead of just a negative reaction that might be obtained with only CK5 (and/or p63). Of note, this latter rationale has been used to argue (successfully) for using amethylacyl-CoA racemase in the evaluation of atypical foci in prostate needle biopsy material, a widely accepted practice in contemporary surgical pathology.…”
Section: Discussionmentioning
confidence: 99%
“…8,16,17 Such expression, combined with decreased/absent high-molecular weight CK expression, has been used to further help distinguish atypical ductal hyperplasia and ductal carcinoma in-situ from usual ductal hyperplasia. There are, however, no studies that systematically evaluate the expression of such low-molecular weight CKs in papillary lesions of the breast.…”
mentioning
confidence: 99%
“…4 Recently, Abdel-Fatah et al proposed a ''low-grade mammary neoplasia family'' hypothesis that includes columnar cell lesions as a precursor lesion. 5 This hypothesis is based on molecular linkage analyses available in the literature, as well as a comprehensive morphologic study comparing the association of different putative precursor lesions and the development of some special types of low-grade invasive mammary carcinoma. These analyses were based on columnar cell lesions coexisting with more advanced lesions in the same specimen.…”
Section: Introductionmentioning
confidence: 99%
“…18 Molecular studies have shown similar genetic alterations in flat epithelial atypia, atypical hyperplasia, and low-grade carcinoma in the same tissue section, suggesting that flat epithelial atypia may be a non-obligate precursor in a low-grade breast neoplasia pathway. 19,20 In long-term follow-up studies of open biopsies, the risk associated with columnar cell lesions and flat epithelial atypia alone appears to be lower than the risk associated with atypical ductal or atypical lobular hyperplasia. 16,17 In a prior series from our institution, we reported a series of 31 cases from 1998 to 2003, with available follow-up excisions, 4 (12.9%) of which contained carcinoma.…”
mentioning
confidence: 99%